A Kajian Cerita Rakyat Lokal "Budak Pahatu" dengan pendekatan Etnolinguistik sebagai Bahan Ajar Membaca pada Peserta Didik fase D di SMP Yayasan Atikan Sunda Bandung: KAJIAN CERITA RAKYAT LOKAL “BUDAK PAHATU” DENGAN PENDEKATAN ETNOLINGUISTIK SEBAGAI BAHAN AJAR MEMBACA PADA PESERTA DIDIK FASE D DI SMP YAYASAN ATIKAN SUNDA BANDUNG - Kinan, Kinanti Puspa Arumsari; Nurhayatin, Titin (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This research aims to examine the local folklore "Budak Pahatu" using an ethnolinguistic approach as reading material for 9th-grade students (Phase D) at SMP Yayasan Atikan Sunda Bandung. The background of this research is based on the low reading interest of students towards folklore and the lack of integration of local culture in Indonesian language learning. The ethnolinguistic approach was chosen because it can reveal the relationship between language and culture reflected in the folklore text. The method used is descriptive qualitative with content analysis techniques on the "Budak Pahatu" text. The analysis focuses on semantic aspects, including vocabulary, lexical and cultural meanings, and Sundanese etiquette values contained in the story. The results show that the "Budak Pahatu" story is rich in local cultural elements that can strengthen students' understanding of language and character. This story also contains educational values such as hard work, patience, and respect for parents, which are relevant to be included in teaching materials. Thus, the results of this study can be adapted into reading materials that not only improve literacy skills but also introduce local wisdom to students in a contextual manner.